Effect of a prolonged maximal bout of exercise on visual performance - Shaw, B. S.; Breukelman, G. J.; Millard, L.; Shaw, I. (Asian Journal of Sports Medicine, 2021)
Background: Despite it being purported that acute, prolonged maximal periods of exercise may impair visual performance, little/no research on this topic is forthcoming. In fact, research has demonstrated that sub-maximal and maximal acute exercise may actually improve cognitive and sensory tasks and thus possibly improve visual performance. Objectives: This study aimed to ascertain the influence of an acute, prolonged maximal bout of exercise on visual performance. Methods: A quantitative study was undertaken with 60 untrained males being divided into a control group (CON; n = 30) or treatment group (TRE; n = 30). Both groups completed a baseline vision test battery consisting of accommodation facility, saccadic eye movement, speed of recognition, peripheral awareness, visual memory, and hand-eye coordination using the following tests; Hart Near Far Rock, saccadic eye movement, evasion, accumulator, flash memory and Ball Wall Toss tests. Two weeks later, participants returned for follow-up testing using the same vision test battery, with the TRE participants first engaging in a standardized incremental maximal treadmill protocol immediately prior to their vision testing. Results: Following the incremental maximal treadmill protocol, statistical analyses indicated that statistically significant (P = 0.05) differences existed for accommodation facility, saccadic eye movements, speed of recognition, hand-eye coordination, peripheral awareness, and visual memory between pre-test and after the aerobic treatment (P = 0.00 for all measures). Conclusions: This study indicates that an acute, prolonged maximal bout of running improves visual performance. As such, an appropriate prolonged maximal warm-up may be required as opposed to a standardized and general warm-up when preparing an athlete for visual skills training or for participation in an athletic event that requires optimal visual performance.